Reproductive Cancer Risk Factors in Women With Myotonic Dystrophy (DM): Survey Data From the US and UK DM Registries - Higgs, Cecilia (Front Neurol, 2019)
Introduction: Recent evidence demonstrates that women with myotonic dystrophy type 1 are at increased risk of reproductive organ tumors. However, studies of reproductive cancer risk factors in those patients are lacking. Methods: Using questionnaires, we collected and analyzed personal history information related to cancer risk factors from women enrolled in a UK and US registry for myotonic dystrophy (dystrophia myotonica; DM) patients. Results: The survey was completed by 242 DM type 1 (DM1) and 44 DM type 2 (DM2) women enrolled in the UK Registry (N = 124) and the US National Registry (N = 162). The mean age at DM1 diagnosis was 33.8 years (standard deviation, SD = 13.2) and for DM2 was 49.2 (SD = 13.0). Mean age at survey was 48.7 (SD = 12.8) and 59.1 years (SD = 12.8) for DM1 and DM2, respectively. There were no statistically significant differences between DM1 and DM2 regarding menstrual history or fertility-related factors. Yet, women with DM2 were more likely to have used menopausal hormone therapy (HT) than women with DM1 (52.3 vs. 22.1%, p < 0.0001), and more women with DM2 had a hysterectomy (53.5 vs. 29.5%, p < 0.01). These differences were not statistically significant after age adjustment (OR = 2.00, p = 0.08, and OR = 1.40, p = 0.38, respectively). The frequency of self-reported reproductive organ tumors was not significantly different comparing DM1 to DM2 (p = 0.28). However, the data suggested that women with DM2 appear to have a lower risk of malignant tumors compared to those with DM1 (OR = 0.72, p = 0.69). Discussion: Our study is the first to characterize a wide range of reproductive risk factors in women with DM. We observed no significant differences between DM1 and DM2 in the factors that were evaluated, which suggests that the known excesses of ovarian and endometrial cancer previously reported in women with DM1 cannot be attributed to greater prevalence of standard cancer-related reproductive risk factors. Larger studies evaluating the possible link between reproductive cancer risk factors and risk of tumors in women with DM are needed.